Novel amorphous aluminum hydroxide catalysts for aluminum–water reactions to produce H2 on demand. (14th September 2017) - Newell, Anthony; Thampi, K. Ravindranathan
Abstract: Production of aluminum (Al) through electrolysis is an energy intensive process. Al metal with its very high specific energy density of 28.8 MJ kg −1 can serve as an excellent energy storage vector. Al reacts with water (reaction(1) ) at room temperature producing clean H2 thus providing an alternative to compressed gas storage. (1) 2Al + 6H2 O → 2Al(OH)3 + 3H2 Reaction(1) does not proceed easily due to the presence of a 2–4 nm passive alumina surface layer. Aluminum hydroxide (Al(OH)3 ) catalyst disrupts this layer, sustaining reaction(1) . The present work focuses on the catalysis aspects of reaction(1) by amorphous Al(OH)3 produced by urea hydrolysis of aluminum nitrate. H2 yields of up to 100% were obtained at 45 °C. Spent reaction product mixtures are autocatalytic with successive additions of Al micropowder (MP) yielding up to 133 ml H2 /minute and reaction completion within 10 min at pH ≈ 10. There is an induction time initially due to the presence of dissolved ions, followed by production of H2 . Reaction by-products are easily recyclable back to Al metal through subsequent calcining and electrolysis by the Al refining industry, which constitutes the energy storage part of the cycle. Highlights: Amorphous aluminum hydroxide for catalyzing Al–water reactions was studied. H2 evolution proceeds after an initial induction time. Al–water reaction catalyzed by a spent reaction mixture produces H2 on demand. By-products are easily recyclable back to Al metal.